PEMBANGUNAN APLIKASI PENERIMAAN KARYAWAN BARU BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK LARAVEL (STUDI KASUS: PT. XYZ) - Gabrielle Beauty Linelejan; Nina Setiyawati (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2023)
The Application Program is a system that is often used by many agencies or companies in increasingly advanced times, be it government or private agencies, in carrying out daily work operations related to fast and accurate data presentation. Company PT. XYZ still uses conventional methods in recruiting employees and managing data, therefore a website-based system will be built to help the world of work face competition in the current era of globalization. The method used in this program uses the waterfall model method. This research will produce a recruitment and employee data processing system that utilizes technological developments to help companies and prospective employees so that all stages run more effectively and efficiently.